Pharmacokinetic and pharmacodynamics of xylazine administered to exercised thoroughbred horses. Issue 5 (13th September 2016) - Knych, Heather K.; Stanley, Scott D.; McKemie, Daniel S.; Arthur, Rick M.; Kass, Phil H.
Abstract : There is limited data describing xylazine serum concentrations in the horse and no reports of concentrations beyond 24 hours. The primary goal of the study reported here was to update the pharmacokinetics of xylazine following intravenous (IV) administration in order to assess the applicability of current regulatory recommendations. Pharmacodynamic parameters were determined using PK‐PD modeling. Sixteen exercised adult Thoroughbred horses received a single IV dose of 200 mg of xylazine. Blood and urine samples were collected at time 0 and at various times for up to 96 hours and analyzed using liquid chromatography tandem mass spectrometry. Xylazine serum concentrations were best fit by a 3‐compartment model. Mean ± SEM systemic clearance, volume of distribution at steady state, beta half‐life and gamma half‐life were 12.7 ± 0.735 mL/min/kg, 0.660 ± 0.053 L/kg, 2.79 ± 0.105 hours and 26.0 ± 1.9, respectively. Immediately following administration, horses appeared sedate as noted by a decrease in chin‐to‐ground distance, decreased locomotion and decreased heart rate (HR). Sedation lasted approximately 45 minutes. Glucose concentrations were elevated for 1‐hour post administration. The EC50 (IC50) was 636.1, 702.2, 314.1 and 325.7 ng/mL for HR, atrioventricular block, chin‐to‐ground distance and glucose concentrations, respectively. The Emax (Imax) was 27.3 beats per minute, 47.5%, 42.4 cm and 0.28 mg/dL for HR, atrioventricular block, chin‐to‐ground distance and glucose concentrations, respectively. Pharmacokinetic parameters differ from previous reports and a prolonged detection time suggests that an extended withdrawal time, beyond current regulatory recommendations, is warranted to avoid inadvertent positive regulatory findings in performance horses. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Following administration of 200 mg of xlazine, 10 of the 16 horses studied had serum concentrations in excess of the current ARCI recommended regulatory threshold (0.01 ng/mL) at 48 hours suggesting that this drug should be used cautiously in race horses and an extended withdrawal time may be warranted to avoid inadvertent positive regulatory findings. Additionally, administration appears to induce sedation, as evidenced by behavioral assessments, chin‐to‐ground distance and affects on HR and rhythm, which are comparable to higher doses.